A multi-layer composite hemostatic material and a method for preparing the same

CN120550177BActive Publication Date: 2026-10-27JINGCHU UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510621007.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-05-14
Publication Date
2026-10-27
Estimated Expiration
2045-05-14

AI Technical Summary

Technical Problem

[0004]鉴于背景技术中存在的技术问题,本申请提供了一种多层复合型止血材料及其制备方法,旨在解决传统止血材料止血效率低、依赖毒性抗菌成分、结构单一、释放速率不可控、生物相容性不足、降解性差、透气性差的技术问题

Benefits of technology

[0015]本申请实施例的技术方案中,将壳聚糖先采用碱液和微波进行处理,提高了壳聚糖的脱乙酰度,使其脱乙酰度大于95%,突破了传统壳聚糖脱乙酰度范围,达到增强正电荷密度,提升止血效率的目的。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application provides a multilayer composite hemostatic material and a preparation method thereof, and belongs to the technical field of biomedical hemostatic materials, wherein the multilayer composite hemostatic material comprises a hemostatic inner layer, an antibacterial and breathable middle layer and a protective support outer layer which are sequentially stacked; the hemostatic inner layer comprises superfine chitosan fiber electrospun membrane and a hemostatic agent coated on the surface of the superfine chitosan fiber electrospun membrane, the hemostatic agent comprises Chinese herbal medicine powder and carboxymethyl cellulose hydrogel; the antibacterial and breathable middle layer comprises a polyurethane foam layer and a PEG-CS / tea polyphenol composite sponge layer, the polyurethane foam layer is in contact with the superfine chitosan fiber electrospun membrane; the protective support outer layer comprises a regenerated cellulose layer and a polytetrafluoroethylene film, and the regenerated cellulose layer is in contact with the PEG-CS / tea polyphenol composite sponge layer. The application adopts a three-layer gradient structure design, the hemostatic inner layer, the antibacterial and breathable middle layer and the protective support outer layer are in synergistic cooperation, and the effects of efficient hemostasis, antibiosis, breathability and support protection are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of biomedical hemostatic materials technology, specifically to a multilayer composite hemostatic material and its preparation method. Background Technology

[0002] Traditional hemostatic materials generally suffer from the following problems: ① Low hemostatic efficiency: Insufficient positive charge density limits the material's ability to adsorb coagulation factors and rapidly activate platelet aggregation. ② Reliance on toxic antibacterial components: The use of antibacterial agents such as nano-silver poses a risk of biotoxicity, potentially affecting wound healing or causing inflammation. ③ Structural uniformity: Most are single-layer structures, lacking functional layered design, making it impossible to simultaneously achieve rapid hemostasis, antibacterial properties, and long-term protection. ④ Uncontrollable release rate: For sustained-release materials such as calcium alginate, the calcium ion release rate is difficult to precisely control, affecting coagulation efficacy. ⑤ Insufficient biocompatibility: Some materials are prone to causing allergic reactions or foreign body rejection, leading to secondary wound damage or infection risks. ⑥ Poor degradation performance: Non-degradable materials require secondary surgery for removal, or the degradation rate does not match the healing cycle, leaving residues that cause inflammation. ⑦ Poor fit and breathability: High material hardness or low porosity makes it difficult to fit irregular wounds, and insufficient breathability easily leads to moisture and infection.

[0003] Traditional hemostatic materials cannot meet the urgent need for rapid, safe, and efficient hemostatic materials in scenarios such as trauma emergency care and surgery. Summary of the Invention

[0004] In view of the technical problems existing in the background art, this application provides a multilayer composite hemostatic material and its preparation method, aiming to solve the technical problems of traditional hemostatic materials such as low hemostatic efficiency, dependence on toxic antibacterial components, simple structure, uncontrollable release rate, insufficient biocompatibility, poor degradability, and poor air permeability.

[0005] In a first aspect, embodiments of this application provide a multilayer composite hemostatic material, comprising a hemostatic inner layer, an antibacterial and breathable middle layer, and a protective and supportive outer layer stacked sequentially; the hemostatic inner layer comprises an ultrafine chitosan fiber electrospun membrane and a hemostatic agent coated on its surface, the hemostatic agent comprising traditional Chinese medicine powder and carboxymethyl cellulose hydrogel; the antibacterial and breathable middle layer comprises a polyurethane foam layer and a PEG-CS / tea polyphenol composite sponge layer, the polyurethane foam layer being in contact with the ultrafine chitosan fiber electrospun membrane; the protective and supportive outer layer comprises a regenerated cellulose layer and a polytetrafluoroethylene film, the regenerated cellulose layer being in contact with the PEG-CS / tea polyphenol composite sponge layer.

[0006] In the technical solution of this application embodiment, the hemostatic inner layer includes an ultrafine chitosan fiber electrospun membrane and a hemostatic agent. The ultrafine chitosan fiber electrospun membrane has a high positive charge density, which can quickly activate platelet aggregation and improve hemostatic efficiency. The hemostatic agent includes traditional Chinese medicine powder and carboxymethyl cellulose hydrogel. The hemostatic agent part comes into contact with the patient's wound. The traditional Chinese medicine powder is wrapped with carboxymethyl cellulose hydrogel. The hydrogel material is relatively soft, which can make the hemostatic material fit the skin better and improve the patient's comfort. In addition, the traditional Chinese medicine powder can play a role in hemostasis and anti-inflammation.

[0007] The antibacterial and breathable middle layer consists of a polyurethane foam layer and a PEG-CS / tea polyphenol composite sponge layer. PEG-grafted chitosan (PEG-CS) is used as a carrier. PEG has good hydrophilicity, which can improve the material's liquid absorption capacity and help absorb blood. Tea polyphenol-chitosan chelate is used instead of traditional nano-silver as an antibacterial agent. It achieves natural antibacterial properties through the combination of phenolic hydroxyl groups and amino groups, avoiding the risk of biotoxicity, promoting wound healing, and preventing inflammation. The polyurethane foam layer's rich open-cell structure ensures gas exchange between the wound and the outside environment, maintaining a dry environment for the wound and preventing infection.

[0008] The protective outer layer consists of a regenerated cellulose layer and a polytetrafluoroethylene (PTFE) film. The PTFE film is waterproof, blocking external moisture and bacterial invasion, and also has good breathability, further ensuring the dryness and ventilation of the material's interior. Secondly, a regenerated cellulose layer is prepared using regenerated cellulose (an environmentally friendly plastic) and gelatin. Gelatin has hemostatic properties, providing a physical barrier for the wound and promoting platelet adhesion and aggregation.

[0009] In some embodiments, the PEG-CS / tea polyphenol composite sponge layer also includes PLGA-encapsulated hydroxyapatite microspheres.

[0010] In the technical solution of this application embodiment, the outer layer of the PLGA-coated hydroxyapatite microspheres is a PLGA coating layer (a biodegradable plastic: polylactic acid-glycolic acid copolymer), and the inner layer is hydroxyapatite. Its function is to use PLGA to coat the hydroxyapatite microspheres (a source of calcium ions), so that calcium is released slowly instead of all at once. This can control the drug effect to take effect slowly and prolong the clotting time of the hemostatic material.

[0011] Secondly, embodiments of this application provide a method for preparing a multilayer composite hemostatic material, comprising the following steps: The traditional Chinese medicine powder and PVA were dispersed in a sodium carboxymethyl cellulose solution, and a carboxymethyl cellulose hydrogel hemostatic agent containing traditional Chinese medicine was prepared by cyclic thawing and freezing. A hemostatic agent is coated onto an ultrafine chitosan fiber electrospun membrane to form a hemostatic inner layer; Chitosan was dispersed in an acetic acid solution, polyethylene glycol diglycidyl ether was added, the mixture was stirred and reacted, and then freeze-dried to obtain PEG-CS. Hydroxyapatite microspheres coated with PEG-CS, tea polyphenols and PLGA were dispersed in water and then freeze-dried in a directional manner to obtain a PEG-CS / tea polyphenol composite sponge layer. The polyurethane foam layer has grooves, and the PEG-CS / tea polyphenol composite sponge layer is embedded in the grooves to obtain an antibacterial and breathable middle layer; Regenerated cellulose is blended with gelatin, cast into a film, and then cured by ultraviolet crosslinking to obtain a regenerated cellulose layer; A protective and support outer layer is obtained by bonding a polytetrafluoroethylene film to a regenerated cellulose layer. The hemostatic inner layer, the antibacterial and breathable middle layer, and the protective and supportive outer layer are sutured together to obtain a multi-layered composite hemostatic material.

[0012] In some embodiments, the mass ratio of traditional Chinese medicine powder to sodium carboxymethyl cellulose is (2~5):(10~20).

[0013] In some embodiments, the herbal powder includes at least one of Bletilla striata, Panax notoginseng, Salvia miltiorrhiza, Schizonepeta tenuifolia, Sargentodoxa cuneata, Caesalpinia sappan, and Celastrus orbiculatus.

[0014] In some embodiments, the preparation method of ultrafine chitosan fiber electrospun membrane includes the following steps: dispersing chitosan in 40% NaOH solution, microwave treatment at 800W for 10 min, filtering and drying to obtain chitosan with high degree of deacetylation; High-degree-of-deacetylation chitosan was dissolved in trifluoroacetic acid / dichloromethane, and then electrospun and treated with argon plasma to obtain an ultrafine chitosan fiber electrospun membrane.

[0015] In the technical solution of this application embodiment, chitosan is first treated with alkaline solution and microwave, which increases the degree of deacetylation of chitosan to greater than 95%, breaking through the traditional range of chitosan deacetylation, thereby achieving the purpose of enhancing positive charge density and improving hemostasis efficiency.

[0016] In some embodiments, the mass ratio of PEG-CS, tea polyphenols and PLGA-encapsulated hydroxyapatite microspheres is 10:1:1.22.

[0017] In some embodiments, the preparation method of PLGA-coated hydroxyapatite microspheres includes the following steps: dispersing hydroxyapatite microspheres and PLGA in dichloromethane at a mass ratio of 1:1, stirring and emulsifying, and then centrifuging and drying to obtain PLGA-coated hydroxyapatite microspheres.

[0018] In the technical solution of this application embodiment, PLGA-coated hydroxyapatite microspheres are prepared by emulsification-solvent evaporation method. The PLGA coating layer can be gradually degraded, so that calcium ions in the hydroxyapatite microspheres are slowly released, thus solving the problem of rapid release of hydroxyapatite microspheres.

[0019] In some embodiments, the directional freeze-drying step is as follows: First stage: Cooling from room temperature to -196℃ at a rate of 10~20℃ / min; Second stage: heating from -196℃ to -80℃ at a rate of 5~10℃ / min; The third stage: heating from -80℃ to -40℃ at a rate of 2~5℃ / min.

[0020] In the technical solution of this application embodiment, liquid nitrogen gradient cooling is used to form a vertical through-hole structure with a porosity of 95% in the PEG-CS / tea polyphenol composite sponge layer.

[0021] In some embodiments, the ultraviolet crosslinking conditions are: at a wavelength of 365 nm and a wavelength of 10 mW / cm². 2 Perform UV crosslinking for 5 min under the specified conditions.

[0022] The advantages of this application, which differ from existing technical solutions, include: This invention employs a three-layer gradient structure design, with the hemostatic inner layer, antibacterial and breathable middle layer, and protective and supportive outer layer working synergistically to achieve highly efficient hemostasis, antibacterial properties, breathability, and protective support. The multi-layer composite hemostatic material in this invention significantly improves hemostatic efficiency; in vitro coagulation tests (PT / APTT) show a hemostasis time of <2 minutes, 50% shorter than traditional materials; in a rat liver penetrating injury model, the hemostasis time is <90 seconds, superior to Celox hemostatic powder. It exhibits excellent antibacterial properties, with the tea polyphenol-chitosan system showing an inhibition rate of >99% against Escherichia coli and Staphylococcus aureus, meeting ISO 22196 standards. It also demonstrates good biocompatibility, passing the full set of ISO 10993 tests, with a cell viability rate >95%.

[0023] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, the following are specific embodiments of this application. Detailed Implementation

[0024] The embodiments of the technical solution of this application will be described in detail below. The following embodiments are only used to illustrate the technical solution of this application more clearly, and are therefore only examples, and should not be used to limit the scope of protection of this application.

[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms “comprising” and “having”, and any variations thereof, in the specification and claims of this application are intended to cover non-exclusive inclusion.

[0026] The following are some specific embodiments. It should be noted that the embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.

[0027] I. Preparation Method Example 1 A method for preparing a multilayer composite hemostatic material includes the following steps: (1) Chitosan (initial deacetylation degree of 90%) was dispersed in 40% NaOH solution and microwaved at 800W for 10min. After filtration and drying, high deacetylation degree chitosan was obtained. The high deacetylation degree chitosan was dissolved in trifluoroacetic acid / dichloromethane (7:3) and electrospun (electrospinning parameters: voltage 25kV, receiving distance 20cm). After electrospinning, argon plasma was used for treatment for 5min (power 50W, time 5min) to obtain ultrafine chitosan fiber electrospun membrane.

[0028] (2) Slowly and evenly sprinkle 20g of sodium carboxymethyl cellulose into 1000mL of water in a mixing tank equipped with a stirring device. The concentration of sodium carboxymethyl cellulose solution is 2%. At the same time, turn on the stirring device and stir at a speed of 1300 r / min for 1 hour to ensure complete dissolution. Then add 3g of PVA, 3.5g of Bletilla striata, and 3.5g of Panax notoginseng powder in a mass ratio of 3:7 to the sodium carboxymethyl cellulose solution and continue to stir evenly. Repeat the freeze-thaw cycle 3 times to obtain a carboxymethyl cellulose hydrogel hemostatic agent containing powders of Bletilla striata, Panax notoginseng, and other traditional Chinese medicines.

[0029] A hemostatic agent was coated onto an ultrafine chitosan fiber electrospun membrane to form a hemostatic inner layer, with a coating thickness of 0.2 mm.

[0030] (3) Disperse hydroxyapatite microspheres and PLGA in dichloromethane at a mass ratio of 1:1, emulsify by stirring, centrifuge and dry to obtain PLGA-coated hydroxyapatite microspheres.

[0031] Chitosan was dispersed in a 1% acetic acid solution, and polyethylene glycol diglycidyl ether was added. The molar ratio of chitosan to polyethylene glycol diglycidyl ether was 1:0.5. The mixture was reacted at 40°C for 6 hours, and after dialysis and freeze-drying, PEG-CS was obtained. Hydroxyapatite microspheres coated with PEG-CS, tea polyphenols, and PLGA were dispersed in water at a mass ratio of 10:1:1.22. The PEG-CS / tea polyphenol composite sponge layer was obtained by directional freeze-drying using liquid nitrogen gradient cooling.

[0032] The steps of directional freeze drying are as follows: Phase 1: Cooling from room temperature to -196℃ at a rate of 20℃ / min; Second stage: heating from -196℃ to -80℃ at a rate of 5℃ / min; The third stage: heating from -80℃ to -40℃ at a rate of 2℃ / min.

[0033] The polyurethane foam layer has grooves, and the PEG-CS / tea polyphenol composite sponge layer is embedded in the grooves to obtain an antibacterial and breathable middle layer.

[0034] (4) Regenerated cellulose and gelatin were blended at a mass ratio of 5:2, cast into a film, and then cured by ultraviolet crosslinking. The ultraviolet crosslinking conditions were: 365nm wavelength, 10mW / cm 2 Under the specified conditions, UV crosslinking was performed for 5 minutes to obtain a regenerated cellulose layer.

[0035] A protective and support outer layer is obtained by bonding a polytetrafluoroethylene film to a regenerated cellulose layer. (5) The hemostatic inner layer, the antibacterial and breathable middle layer and the protective support outer layer are sutured together to obtain a multi-layer composite hemostatic material.

[0036] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that in step (1), the chitosan was not microwave-treated and was directly used for electrospinning to obtain a chitosan fiber electrospinned membrane. The other steps are the same as in Example 1.

[0037] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that no Chinese herbal medicine powder was added in step (2), while the other steps are the same as in Example 1.

[0038] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that in step (3), the hydroxyapatite microspheres encapsulated by PLGA are replaced with calcium alginate, while the other steps are the same as in Example 1.

[0039] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that in step (4), tea polyphenols are replaced with an equal mass of nano silver, while the other steps are the same as in Example 1.

[0040] Comparative Example 5 In Comparative Example 5, traditional hemostatic materials were used, specifically Type I hemostatic materials from Shijiazhuang Yishengtang Medical Supplies Co., Ltd.

[0041] II. Testing Methods 1. The in vitro coagulation and hemostasis time (PT / APTT) test method refers to ISO 10993-4 (blood compatibility testing for medical devices) and the coagulation test specifications in the Chinese Pharmacopoeia.

[0042] Experimental steps: Sample preparation: The material was cut into 1 cm × 1 cm segments and soaked in 0.9% physiological saline (37℃, 1 hour) to prepare the extract.

[0043] Plasma processing: Fresh whole blood anticoagulated with sodium citrate was collected from healthy volunteers and the plasma was separated by centrifugation (3000 rpm, 15 min).

[0044] Coagulation time measurement: PT (Prothrombin Time): Mix 100 μL of plasma with 50 μL of material extract, add PT reagent (containing thromboplastin and Ca²⁺), and record the fibrin clot formation time.

[0045] APTT (Activated Partial Thromboplastin Time): Mix 100 μL of plasma with 50 μL of material extract, add APTT reagent (containing ellagic acid and phospholipids), incubate for 3 min, then add CaCl2 solution (0.025 M) and record the clot time.

[0046] 2. Methods for detecting venous bleeding cessation time (animal model): Refer to the "Guidelines for the Operation of Laboratory Animal Surgery" and ISO 10993-2 (Animal Welfare and Experimental Design).

[0047] Experimental steps: Animal model: SD rats (weighing 200±20 g) were selected. After anesthesia, the femoral artery and vein of the rats were completely removed to simulate venous bleeding.

[0048] Material application: Apply hemostatic material (1 cm × 1 cm) directly to the wound and apply constant pressure (50 mmHg).

[0049] Determining the time to stop bleeding: Complete hemostasis is defined as the absence of blood seepage through the gauze and the absence of active bleeding from the wound. The time is recorded.

[0050] 3. Antibacterial rate test (Escherichia coli / Staphylococcus aureus) test method: according to ISO 22196 (quantitative test of antibacterial activity of antimicrobial materials) and ASTM E2149 (dynamic contact method).

[0051] Experimental steps: Preparation of bacterial culture: Escherichia coli (ATCC 25922) and Staphylococcus aureus (ATCC 6538) were inoculated into LB liquid medium and cultured in a shaker at 37°C until the logarithmic growth phase (OD600≈0.5).

[0052] The bacterial concentration was adjusted to 1×10 6 CFU / mL.

[0053] Sample preparation: Incubate the material (1 cm × 1 cm) with 1 mL of bacterial solution (37℃, 24 h).

[0054] Colony counting: 100 μL of incubation solution was serially diluted and spread onto agar plates, incubated at 37°C for 24 h, and the number of colonies was counted.

[0055] Antibacterial rate calculation: Antibacterial rate (%) = (Number of colonies in the control group - Number of colonies in the experimental group - Number of colonies in the control group) × 100% Quality control requirements: The number of colonies in the blank control group must be ≥1×10⁻⁶ 5 CFU / mL, the experiment was repeated 3 times.

[0056] 4. Cell viability (MTT method) detection method: Refer to ISO 10993-5 (in vitro cytotoxicity test) and GB / T16886.5.

[0057] Experimental steps: Preparation of extract: The material was immersed in DMEM medium (37℃, 24h) according to the surface area / extraction medium ratio (3 cm² / mL).

[0058] Cell culture: L929 mouse fibroblasts were seeded in 96-well plates (1×10⁻⁶ cells / well). 4 (cells / well), cultured at 37℃ and 5% CO2 for 24 h.

[0059] Toxicity exposure: Remove the original culture medium, add 100 μL of material extract, and continue culturing for 24 h.

[0060] MTT staining: Add 20 μL of MTT solution (5 mg / mL) to each well, incubate for 4 h, then aspirate the liquid and add 150 μL of LDMSO to dissolve the formazan crystals.

[0061] Absorbance measurement: The absorbance at 570 nm was measured using a microplate reader (reference wavelength 630 nm), and the relative cell viability was calculated. Survival rate (%) = (OD value of experimental group - OD value of blank group) / (OD value of negative control group - OD value of blank group) × 100% Quality control requirements: The survival rate of the negative control (pure culture medium) should be ≥90%, and the survival rate of the positive control (containing 10% DMSO) should be ≤20%.

[0062] III. Analysis of Test Results for Each Embodiment and Comparative Example The multilayer composite hemostatic materials prepared in Example 1 and Comparative Examples 1-5 were tested, and the test results are shown in Table 1 below.

[0063] Table 1. Test results of the multilayer composite hemostatic materials prepared in Example 1 and Comparative Examples 1-5

[0064] As shown in Table 1, the data in Table 1 demonstrates that the present invention achieves a comprehensive breakthrough in hemostasis efficiency, antibacterial performance, and biosafety through the synergistic design of the hemostatic inner layer (highly charged chitosan + traditional Chinese medicine), the antibacterial middle layer (tea polyphenol-PEG-CS + PLGA microspheres), and the protective outer layer (regenerated cellulose + PTFE). This effectively solves the core defects of traditional hemostatic materials, such as slow hemostasis, high toxicity, and simple structure.

[0065] As shown in Table 1, the hemostatic material of Example 1 is significantly superior to the other pairs in terms of in vitro clotting time (1.8 min), intravenous hemostasis time (1.5 min), antibacterial rate (99.5% for Escherichia coli and 99.3% for Staphylococcus aureus), and cell survival rate (96%).

[0066] In Comparative Example 1, the hemostasis time was prolonged for untreated chitosan (3.2 min in vitro, 3.0 min intravenously), indicating that microwave treatment increased the degree of deacetylation of chitosan (>95%) and enhanced the positive charge density, thereby accelerating platelet aggregation.

[0067] In Comparative Example 2, no herbal powder was added. The hemostasis time (2.5 min in vitro, 2.2 min in intravenous) and antibacterial rate (99.0%) were lower than those in Example 1, indicating that Bletilla striata, Panax notoginseng and other herbal medicines improved the overall performance through synergistic hemostasis and anti-inflammatory effects.

[0068] In Comparative Example 3, calcium alginate was used instead of PLGA microspheres, which prolonged the hemostasis time (2.8 min in vitro, 2.5 min in the vein). This was because the release of calcium ions from calcium alginate was uncontrollable, while the PLGA-encapsulated microspheres could achieve sustained release and prolong the coagulation time. The cell viability decreased to 93%, possibly due to the excessively high local concentration of calcium alginate degradation products.

[0069] In Comparative Example 4, the use of nano-silver to replace tea polyphenols slightly improved the antibacterial rate, but the cell survival rate decreased significantly to 85%, confirming the cytotoxic risk of nano-silver. In contrast, the tea polyphenol-chitosan system combines antibacterial safety with biocompatibility.

[0070] In Comparative Example 5, traditional hemostatic materials were used, and all indicators were inferior to those in Example 1 (e.g., in vitro hemostasis time of 3.0 min and cell survival rate of 88%). The invented multilayer composite hemostatic material is significantly superior to existing hemostatic materials and has obvious advantages in rapid hemostasis, long-lasting antibacterial effect, and biosafety.

[0071] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.

Claims

1. A multi-layer composite hemostatic material, characterized in that, The device comprises a hemostatic inner layer, an antibacterial and breathable middle layer, and a protective and supportive outer layer, which are stacked sequentially. The hemostatic inner layer includes an ultrafine chitosan fiber electrospun membrane and a hemostatic agent coated on its surface, wherein the hemostatic agent includes traditional Chinese medicine powder and sodium carboxymethyl cellulose hydrogel. The antibacterial and breathable middle layer includes a polyurethane foam layer and a PEG-CS / tea polyphenol composite sponge layer, wherein the polyurethane foam layer is in contact with the ultrafine chitosan fiber electrospun membrane. The protective and supportive outer layer includes a regenerated cellulose layer and a polytetrafluoroethylene film, wherein the regenerated cellulose layer is in contact with the PEG-CS / tea polyphenol composite sponge layer.

2. The multilayer composite hemostatic material according to claim 1, characterized in that, The PEG-CS / tea polyphenol composite sponge layer also includes PLGA-encapsulated hydroxyapatite microspheres.

3. A method for preparing the multilayer composite hemostatic material as described in claim 2, characterized in that, Includes the following steps: The traditional Chinese medicine powder and PVA were dispersed in a sodium carboxymethyl cellulose solution, and a sodium carboxymethyl cellulose hydrogel hemostatic agent containing traditional Chinese medicine was prepared by cyclic thawing and freezing. The hemostatic agent is coated onto an ultrafine chitosan fiber electrospun membrane to form a hemostatic inner layer. Chitosan was dispersed in an acetic acid solution, polyethylene glycol diglycidyl ether was added, the mixture was stirred and reacted, and then freeze-dried to obtain PEG-CS. The PEG-CS, tea polyphenols and PLGA-encapsulated hydroxyapatite microspheres were dispersed in water and then freeze-dried in a directional manner to obtain a PEG-CS / tea polyphenol composite sponge layer. The polyurethane foam layer has grooves, and the PEG-CS / tea polyphenol composite sponge layer is embedded in the grooves to obtain an antibacterial and breathable middle layer. The regenerated cellulose is blended with gelatin, cast into a film, and then cured by ultraviolet crosslinking to obtain a regenerated cellulose layer. The polytetrafluoroethylene film is bonded to the regenerated cellulose layer to obtain a protective and support outer layer. The hemostatic inner layer, antibacterial and breathable middle layer, and protective support outer layer are sutured together to obtain a multi-layer composite hemostatic material.

4. The method for preparing the multilayer composite hemostatic material according to claim 3, characterized in that, The mass ratio of the Chinese herbal powder to sodium carboxymethyl cellulose is (2~5):(10~20).

5. The method for preparing the multilayer composite hemostatic material according to claim 4, characterized in that, The herbal powder includes at least one of Bletilla striata, Panax notoginseng, Salvia miltiorrhiza, Schizonepeta tenuifolia, Sargentodoxa cuneata, Sappanwood, and Celastrus orbiculatus.

6. The method for preparing the multilayer composite hemostatic material according to claim 3, characterized in that, The preparation method of the ultrafine chitosan fiber electrospun membrane includes the following steps: dispersing chitosan in a 40% NaOH solution, microwave treatment at 800W for 10 minutes, filtering and drying to obtain chitosan with high degree of deacetylation; The high degree of deacetylation chitosan was dissolved in trifluoroacetic acid / dichloromethane, and then electrospun and treated with argon plasma to obtain an ultrafine chitosan fiber electrospun membrane.

7. The method for preparing the multilayer composite hemostatic material according to claim 3, characterized in that, The mass ratio of the PEG-CS, tea polyphenols and PLGA-encapsulated hydroxyapatite microspheres is 10:1:1.

22.

8. The method for preparing the multilayer composite hemostatic material according to claim 3, characterized in that, The preparation method of the PLGA-encapsulated hydroxyapatite microspheres includes the following steps: dispersing hydroxyapatite microspheres and PLGA in dichloromethane at a mass ratio of 1:1, stirring and emulsifying, centrifuging and drying to obtain PLGA-encapsulated hydroxyapatite microspheres.

9. The method for preparing the multilayer composite hemostatic material according to claim 3, characterized in that, The directional freeze-drying step is as follows: First stage: Cooling from room temperature to -196℃ at a rate of 10~20℃ / min; Second stage: heating from -196℃ to -80℃ at a rate of 5~10℃ / min; The third stage: heating from -80℃ to -40℃ at a rate of 2~5℃ / min.

10. The method for preparing the multilayer composite hemostatic material according to claim 3, characterized in that, The ultraviolet crosslinking conditions are: at a wavelength of 365 nm and a wavelength of 10 mW / cm². 2 Perform UV crosslinking for 5 min under the specified conditions.